Correlation between clinically and histopathologically measured tumor width in basal cell carcinoma - Gajić, Branislava; Lučić, Silvija; Milošević, Nataša; Božić, Srna; Ivkov Simić, Milana; Nišavić, Miloš; Roš, Tatjana; Levakov, Olivera (Vojnosanitetski pregled, 2025)
Introduction/Aim. Basal cell carcinoma (BCC) is the most common malignant skin tumor in fair-skinned populations. Although it has low metastatic potential, it can be highly locally invasive and, in addition to impairing function, may even pose a threat to life itself. The majority of BCCs can be successfully reated by classical surgical excision with appropriate safety margins. The aim of this study was to evaluate the correlation between clinical and histopathological tumor width in excised BCCs. Methods. A prospective clinical and histopathological study included 45 subjects consecutively examined at the Department of Dermatologic Surgery and Skin Tumors, University Clinical Center of Vojvodina, Novi Sad, Serbia, with a total of 60 primary BCC specimens obtained by classical surgical excision. Medical history was recorded, and dermatological examination was performed. Prior to the excisional biopsy, an incision was made along the edge of the clinically visible tumor to the level of the papillary dermis, and the standard recommended safety margin was added. Histopathological assessment involved microscopic analysis at various magnifications. The histopathological tumor width was measured using a millimeter ocular. The total clinically estimated tumor width was determined as the distance between the two stated skin incisions, and the distance from the incision to the histopathological tumor margin was also recorded. Results. A statistically significant correlation was found between clinically determined and microscopically measured total tumor width (p < 0.05). The mean clinically estimated width was 9.55 ± 5.13 mm, while the histopathological width was 7.98 ± 4.75 mm. The statistically determined difference between the clinically marked and microscopically measured tumor width was less than 2.0 mm in 96.7% of cases, i.e., in 88.4% of cases, this difference in assessment was 1.0 mm or less. Conclusion. There is a positive correlation between the clinically assessed and histopathologically verified width of the BCC.
Keywords: carcinoma, basal cell; dermoscopy; histological techniques; skin neoplasms.